Allelopathic effects of Margalefidinium polykrikoides on the growth of Pyrodinium bahamense in different nutrient concentrations - Al-Has, Asilah; Mohammad Noor, Normawaty; M. Shaleh, Sitti Raehanah; Mustapha, Shuhadah; Darnis, Deny Susanti; Ayub, Mohd Nor Azman; Adam, Aimimuliani; Mustakim, Ghaffur Rahim (International Society for the Study of Harmful Algal Blooms., 2022)
Co-occurrence of the dinoflagellates Margalefidinium polykrikoides, a known fish killer, and the neurotoxic species Pyrodinium bahamense is commonly observed in the coastal waters of Sabah, Malaysia. During most of these events, M. polykrikoides dominated the bloom, apparently suppressing the growth of P. bahamense. To increase our understanding on the nutrient conditions of this phenomenon, a study was conducted to explore the interaction between these species. The specific aim was to document the allelopathic effects, if any, of M. polykrikoides o n P. bahamense when varying ratios of the two species were co-cultured under different nitrogen (N) and phosphorus (P) concentrations. The bioassay experiments started with three cell abundance proportions, which were 5:5 (500 cells mL-1 of each species, M. polykrikoides, and P. bahamense); 1:5 (100 cells mL-1 of M. polykrikoides and 500 cells mL-1 of P. bahamense); and 5:1 (500 cells mL-1 of M. polykrikoides and 100 cells mL-1 of P. bahamense). Additionally, culture filtrates (10, 20 and 50 mL) from the late exponential phase of M. polykrikoides were added to 150 mL of P. bahamense to determine if cell filtrates were allelopathic. Results indicate that M. polykrikoides was allelopathic to P. bahamense when nutrients were abundant, but not when nutrients were limiting or N was limiting relative P. The production of allelopathic compounds was supported by abnormal morphological changes in P. bahamense when co-cultured with M. polykrikoides. This capacity to suppress P. bahamense growth, combined with the inherently faster growth rate of M. polykrikoides relative to P. bahamense can account for why M. polykrikoides forms nearly monospecific blooms when nutrients are high. The filtration studies indicated the allelopathic capacity of M. polykrikoides required direct cell contact or that the allelopathic compounds degraded rapidly and were inactive when added to P. bahamense cultures. These results are important in understanding the bloom mechanisms of these two harmful algal blooms (HABs) species.